Ciencias forenses y transexualidad : concepciones y procesos en Colombia (2021)
Forensic sciences are the technical arm of justice that seeks through the different techniques and sciences that make up the clarification of violent crimes and victimizing events, bring justice to the victims who are part of a social state of law and their families and loved ones. In this context we find transsexual people, who in Colombia are at great risk due to the gender identity they carry and build throughout their lives. This thesis presents a theoretical framework and an approach to the thoughts and experience of forensic professionals on how transsexual bodies that have been deceased or disappeared in Colombia would address or deal with forensic sciences. For this, interviews were conducted with different forensic experts in the country and an exhaustive investigation was carried out in gender theory and human identification, to propose day-to-day cases and end with conclusions, reflections and proposals from an ethnographic and technical perspective.